Optimization of Protocols for In Vitro Regeneration of Sugarcane (Saccharum officinarum). (28th December 2017) - Jamil, Shakra; Shahzad, Rahil; Talha, Ghulam Mohyuddin; Sakhawat, Ghazala; Sajid-ur-Rahman,; Sultana, Razia; Iqbal, Muhammad Zaffar
Abstract : Sugarcane contributes 60–70% of annual sugar production in the world. Somaclonal variation has potential to enhance genetic variation present within a species. Present study was done to optimize an in vitro propagation protocol for sugarcane. The experiments included four varieties, 9 callus induction media, 27 regeneration media, and 9 root induction media under two-factor factorial CRD. Data were recorded on callus induction, embryogenic callus formation, shoot elongation (cm), root induction, and plant regeneration. Statistically significant differences existed between genotypes and treatments for callus induction (%), embryogenic callus formation (%), shoot elongation (cm), root induction, and plant regeneration (%). All parameters showed dependency on genotypes, culture media, and their interaction. Highest callus induction (95%) embryogenic callus formation (95%) was observed in callus induction media 5. Highest plantlet regeneration (98.9%) capacity was observed in regeneration media 11 whereas maximum shoot elongation (12.13 cm) and root induction (8.32) were observed in rooting media 4. G 1 showed best response for all traits and vice versa for G 4 . Hence it was concluded that G 1, callus induction media 5, regeneration media 11, and rooting media 4 are the best conditions for in vitro propagation of sugarcane.